Public administration, citizen and transparency - Mendoza Juárez, Alfonso (Universidad Nacional del Litoral, 2020)
The aim of this article is aboard the importance of transparency in the democracy like an element indispensable for the effectivity in the citizen’s participation. In this instrument of participation there are the public consultation, the initiative of law, the independent candidacies, however, there are others instruments how the citizens can affect the public life in the region.